2010
DOI: 10.1007/s12223-010-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence of Pseudomonas fluorescens HK44 in the course of encapsulation into silica gel. Effect of methanol

Abstract: The bioluminescence (BLM) and colony-forming units (CFU) of Pseudomonas fluorescens HK44 were monitored during encapsulation into pre-polymerized Si(OMe)₄. The non-induced BLM of free cells was increased in the presence of 0.5-2.5 % MeOH. After mixing silica sol with the cell suspension, both BLM and CFU dropped to 1-3 and 8-18 %, respectively; both remained lowered as long as the silica biofilm contained residual MeOH. The kinetics of MeOH being released from silica biofilms (a thickness of 2-6 mm) were first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The main disadvantages of this biosensor configuration were the length of time needed for preparation of the cell layer and continual changes of analytical responses. In this work, we applied an optimized route toward [19,29,30,34] silica-gel-encapsulation of living bioreporters on to optical fibers. In contrast to physical adsorption, this technique enables reproducible fixation of a desired amount of cells on the top of the optical fiber within an hour [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main disadvantages of this biosensor configuration were the length of time needed for preparation of the cell layer and continual changes of analytical responses. In this work, we applied an optimized route toward [19,29,30,34] silica-gel-encapsulation of living bioreporters on to optical fibers. In contrast to physical adsorption, this technique enables reproducible fixation of a desired amount of cells on the top of the optical fiber within an hour [35].…”
Section: Resultsmentioning
confidence: 99%
“…Cell encapsulation was performed according to a procedure used in previous studies [19,29,30,31]. Briefly, tetramethoxysilane (TMOS, 4.1 g) was stirred with distilled water (2 mL), cooled for 5 min at 4 °C, and 0.1 M HCl (0.5 mL) was then slowly added.…”
Section: Methodsmentioning
confidence: 99%
“…An exponentially growing HK44 culture emits higher non-induced (background) bioluminescence and hence the relative increase upon induction is lower as compared to stationary or starving cultures [48,54]. Bioluminescence also decreases upon interaction with toxic chemicals, including inducers of nah-lux genes in strain HK44 [5457]. It was also demonstrated that HK44 bioluminescence increases upon exposure to organic solvents [54,58].…”
Section: Biosensing With P Fluorescens Hk44mentioning
confidence: 99%
“…This effect is known from other bioluminescent assays [59] and is ascribed to membrane perturbations which, through production of increased levels of free fatty acids, leads to an increased supply of aldehyde substrates for luciferase that are normally limited, although this remains hypothetical. At high concentrations of perturbing chemicals, the negative effect prevails leading to a decrease in bioluminescence (Figure 5) [5457]. …”
Section: Biosensing With P Fluorescens Hk44mentioning
confidence: 99%
See 1 more Smart Citation